2014
DOI: 10.1016/j.atmosenv.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poverty on the relationship between personal exposures and ambient concentrations of air pollutants in Ho Chi Minh City

Abstract: h i g h l i g h t sWe examined the pollutant exposureepoverty relationship in Ho Chi Minh, Vietnam. Personal exposures to particles and NO 2 were higher amongst the poor. Ambient levels poorly reflect personal exposures, in particular for poor residents. In addition to socioeconomic status, behavioral factors determined exposure levels. a b s t r a c t Socioeconomic factors often affect the distribution of exposure to air pollution. The relationships between health, air pollution, and poverty potentially have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Of which, approximately 12 million affected babies are from South Asia (UNICEF, 2017). Young children, especially those from the poor socio-economic background, are most vulnerable to the impacts of toxic air pollutants (Mehta et al, 2014;Perera, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of which, approximately 12 million affected babies are from South Asia (UNICEF, 2017). Young children, especially those from the poor socio-economic background, are most vulnerable to the impacts of toxic air pollutants (Mehta et al, 2014;Perera, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, 44 studies assessing individual exposure based on an individual’s trajectory and variable air quality approach were identified. The majority of the analyzed studies use personal monitoring as the most reliable and accurate way of estimating the pollution levels that an individual is actually exposed to [ 20 , 24 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. Personal monitoring assesses an individual’s exposure based on measuring the concentration of a pollutant, ideally within a person’s breathing zone for a defined time.…”
Section: Spatiotemporal Personal Exposure Assessment: What Are Thementioning
confidence: 99%
“…Past studies indicated that about 2.59 billion persons in the world has no/poor access to appropriate sanitation, meaning they must defecate openly (Global report on human settlements, 2016). Past studies argued that the reason of human prevalent and disaster around the world resulted from ineffective waste generated being disposed (Mehta, 2014;Liu & Gary, 2014;Onibokun & Faniran, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These problems have held back so many developmental efforts in developing countries, mostly in Sub-Saharan Africa (SSA) (Oloruntoba et al, 2014, Aliyu & Amadu, 2017. A diversity of economic and health benefits are related to enhanced water and sanitation (Shuaib et al, 2014;UNCTAD, 2014;Mehta, 2014). Awareness of the health welfares of sanitation is significant because some vital economic gains hang on assessments of health consequences (WEF, 2015).…”
Section: Introductionmentioning
confidence: 99%